Essays in the metaphysics of modality - Plantinga, Alvin (Oxford University Press, 2001)
This volume collects the most important articles on the metaphysics of modality by philosopher Alvin Plantinga. The focus is on such fundamental issues in metaphysics as the nature of abstract objects